The elusive quantifi cation of nitrogen fi xation in xeric shrubs: The case of Adesmia volckmanni, a Patagonian leguminous shrub - Golluscio, Rodolfo (2014)
The comparison of 15N natural abundance (δ15N) between fixing and non-fixing reference species, is the most feasible method for nitrogen fixation studies in xeric shrubs. However, it assumes that both species use the same sources of soil N, the δ15N of such source is clearly different from zero, and the difference between the δ15N of both species is ≥ 5‰. On the other hand, the analysis of the difference between the δ15N of nodules and leaves (Δδ15Nn−l) does not require a reference species. To evaluate the effect of water availability on nitrogen fixation, we analyzed the variation of δ15N and Δδ15Nn−l in watered and unwatered plants of Adesmia volckmanni Phil. (Fabaceae) and Mulinum spinosum (Cav.) Pers. (Apiaceae), formerly proposed as non-fixing reference species. However, we found that M. spinosum was not valid as reference species to study N fixation in Adesmia volckmann because its δ15N was closer to zero than that of the presumably fixing species, suggesting they use different soil N sources. In addition, water availability did not affect biological fixation after watering because both leaf δ15N and Δδ15Nn−l of A. volckmanni did not change either as soil dried up along the growing season nor in response to watering. However, the presence of nodules itself, the δ15N closer to zero than in a former dry year, and the Δδ15Nn−l (+ 1.23‰) suggest that biological fixation could have occurred before watering, probably during early spring.